PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SACHIKO ARTHA NUSANTARA TANGERANG BANTEN - Atalya Samantha Mamahit; Rahmi Andini Syamsuddin (Journal of Research and Publication Innovation, 2025)
This study was carried out with the aim of determining the influence of work stress and work environment on employee performance, both partially and simultaneously at PT Sachiko Artha Nusantara Tangerang Banten. The methods used are descriptive quantitative data used are primary data and secondary data. The sampling technique used saturated sampling and the sample in this study was obtained with a total of 60 respondents. Data analysis techniques include validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, auto correlation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, determinant coefficient test, and hypothesis test. Hypothesis testing the partial work stress variable (X1) obtained Thitung > Ttabel (8.733 > 1.672) and a significant value of 0.000 < 0.05. This means that work stress (X1) has a significant effect on employee performance (Y). The hypothesis test partially of the work environment variable (X2) was obtained by Thcal < Ttable (-1.825 < 1.672) and a significant value of < 0.05. This means that the work environment does not have a significant effect on employee performance (Y). Simultaneously, there is a significant influence of the variables of Work Stress and Work Environment on Employee Performance at PT. Sachiko Artha Nusantara Tangerang Banten, it can be proven from the value of the regression equation Y = 14.113 + 0.768X1 - 0.079X2, that is, the value of the correlation coefficient is obtained of 0.574 and the two variables have a strong relationship.